Large-Scale Flow Photochemical Synthesis of Functionalized trans-Cyclooctenes Using Sulfonated Silica Gel - Darko, Ampofo; Boyd, Samantha J.; Fox, Joseph M. (Synthesis, 2018)
Functionalized trans-cyclooctenes are useful bioorthogonal reagents that are typically prepared using a flow photoisomerization method in which the product is captured by AgNO3 on silica gel. While this method is effective, the leaching of silver can be problematic when scaling up syntheses. It is shown here that Ag(I) immobilized on tosic silica gel can be used to capture trans-cyclooctene products at higher loadings without leaching. It is demonstrated that the sulfonated silica gel can be regenerated and reused with similar yields over multiple runs. Nine different trans-cyclooctenes were synthesized, including those commonly utilized in bioorthogonal chemistry as well as new amine and carboxylic acid derivatives.
Keywords: flow chemistry; photochemistry; trans-cyclooctene; large scale; bioorthogonal